Inspirations - Arca, Nurdan (Turkey, 2006)
The film focuses on the enlightened wisdom of the Ottoman Sufi Sheikh Bedreddin (1359-1416). He was born into the pluralistic environment of the Balkans. A prominent jurist of his time Bedreddin of Simavna defended multicultural co-existence in equality and justice. He was also a dissident daring to criticise the orthodoxies, challenging the existing hierarchies and depicting a spectacular case of dissent in the rich multicultural texture of Blakans and Anatolia.
Keywords: Documentary films